Gender Dysphoria in Iran: legal and Islamic Jurisprudence Perspectives: Gender Dysphoria in Iran - Vahedi, Mostafa; Alimardani, Armin; Behrouzih, Mohammad Reza; Rayejian Asli, Mehrdad (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Gender Dysphoria is the formal diagnosis of psychiatrists that is used to describe a person who has been seriously dissatisfied with his or her gender at birth or the gender role that society considered for them. Some research and studies have been conducted related to investigating social and family dimensions and consequences of this disorder. Surveys and case studies have been done regarding the personality disorders, and personality patterns, and the adaptability of the role and sexual identity of these patients with their new gender, but there are still unanswered questions in this case. Thus, by investigating the legitimacy of sex change surgery in terms of jurisprudence and legal elements before and after sex change, this study tries to remove the ambiguity in this area. Materials and Methods: In this study, using keywords such as sex change, Gender Identity Disorder, and ‘Gender Dysphoria’ in the jurisprudence and legal areas of SID, Google Scholar, Magiran, Noormags databases, the related resources were studied and analyzed. Ethical Considerations: Honesty and trusteeship were taken into consideration in the analysis of information and sources. Findings: There is no single perspective in terms of legitimacy or prohibition of sex-change surgery among scholars and Grand Ayatollahs. Some have permitted sex-change surgery and some others believe that superficial sex change is not permissible without a creatural background. There is also a legal gap not only in the Islamic Penalty Code (IPC) but also in other Iranian laws on the provisions and conditions of sex change. This issue has raised ambiguity in the rights and duties of people seeking sex-change surgery. This is while, in the laws of many other countries, this issue has been explicitly mentioned, and this framework greatly contributes to many people with ‘Gender Dysphoria’ and removes confusion in this regard. Conclusion: In Iranian law, the approval of laws regarding the provision of medical facilities, insurance services and the adoption of clear and transparent rules on the status of marriage, dowry, inheritance, custody, and guardianship of children will remarkably contribute to the process of recognition of people with difficulties in sexual identity among men and women. Also when considering the genetic and biological factors that contribute to Gender Dysphoria, the promotion of the culture of dealing with the phenomenon of sex transfer applicants through raising awareness in the media is felt. *Corresponding Author: Mostafa Vahedi; Email: mostafavahedi38@gmail.com; ORCID: https://orcid.org/0000-0002-2432-5323 Please cite this article as: Vahedi M. Alimardani A. Behrouzih MR. Rayejian Asli M. Gender Dysphoria in Iran: legal and Islamic Jurisprudence Perspectives. Bioeth Health Law J. 2021; 1:1-10 (e4). http://doi.org/10.22037/bhl.v1i1.38128